2017
DOI: 10.1049/mnl.2017.0092
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐exchange synthesis of hollow BiOCl/Bi 2 S 3 hybrids with superior capability for photocatalytic reduction of hexavalent chromium under visible light irradiation

Abstract: BiOCl/Bi 2 S 3 hollow hybrids were synthesised through a mild anion-exchange method from BiOCl microspheres and thiacetamide. X-ray diffraction, scanning electron microscopy, transmission electron microscopy, nitrogen adsorption measurements, ultraviolet-visiblenear-infrared diffuse reflectance spectra, photocurrent, and electrochemical impedance spectroscopy (EIS) were employed to study the composition, structure, and properties of the as-synthesised BiOCl/Bi 2 S 3 hybrids. Compared to pure Bi 2 S 3 and BiOCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In BiOCl/Bi 2 S 3 heterostructure experiments, 2,3,5,[15][16][17][18][19] the researchers are very concerned about the reduction ability of the BiOCl/Bi 2 S 3 heterostructures, such as the reduction of Cr 6+ to Cr 3+ and O 2 to O 2 À ; whereas the reduction ability of hydrogen generation from water, which is one of the significant applications of photocatalysts, 1 has been seldom discussed. For water-splitting to produce hydrogen, although BiOCl/Bi 2 S 3 -(001) and BiOCl/V S -Bi 2 S 3 -(001) heterostructures have suitable band edge positions for overall water-splitting, shown in Fig.…”
Section: The Her Performancementioning
confidence: 99%
See 4 more Smart Citations
“…In BiOCl/Bi 2 S 3 heterostructure experiments, 2,3,5,[15][16][17][18][19] the researchers are very concerned about the reduction ability of the BiOCl/Bi 2 S 3 heterostructures, such as the reduction of Cr 6+ to Cr 3+ and O 2 to O 2 À ; whereas the reduction ability of hydrogen generation from water, which is one of the significant applications of photocatalysts, 1 has been seldom discussed. For water-splitting to produce hydrogen, although BiOCl/Bi 2 S 3 -(001) and BiOCl/V S -Bi 2 S 3 -(001) heterostructures have suitable band edge positions for overall water-splitting, shown in Fig.…”
Section: The Her Performancementioning
confidence: 99%
“…Indeed, constructing BiOCl/Bi 2 S 3 heterostructures in experiments has been demonstrated as a very effective strategy that not only can decrease the recombination of photo-generated carriers but can also improve the visible light absorption, further boosting the photocatalytic performance. [2][3][4][5][6][14][15][16][17][18][19] For example, Jia et al 20 reported that the synthetic BiOCl/Bi 2 S 3 heterostructure exhibits improved optical properties and an enhanced efficient a Guizhou Provincial Key Laboratory of Computational Nano-Material Science, degradation rate of Rhodamine B, compared to single BiOCl and Bi 2 S 3 . Tanveer et al 19 indicated that the BiOCl/Bi 2 S 3 heterostructure exhibits enhanced photocatalytic activity for the degradation of methyl orange due to the highly efficient separation rate of photo-generated electron-hole pairs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations